(3eMGSHI GdJcGdja GdUfGYjIs - (3fhGa(B, (3aNQs ((3YeGf(B:s (3GdOGQ GdYdejI GdOhdjI ddfTQ hGdJhRjY(B,s, 2002)
(3eONd Gdi eMGSHI GdJcGdja, GdGSS GdfXQjI hGdELQGAGJ GdYedjI dhVY fXGe eMGSHI GdJcGdja, eaGgje GdJcdaI hWQb JHhjH YfGUQ hHfhO GdJcGdja GdeNJdaI(B- (3GdfXQjGJ GdGSGSjI dJMejd YfGUQ GdJcGdja RfeGPL GYOGO GdbhGFe hGdMSGHGJ GdNJGejI aj GdefTBJ GdUfGYjI, GdQbGHI Yf JcdaI GdeSJdReGJ GdSdYjI, GdeMGSHI Yf GdGLhQ, GdeMGSHI Yf JcGdja ZjQ GdUfGYjI ZjQ GdeHGTQI, eMGSHI GdJcGdja Ydi CSGS GdGfTWIs
Keywords: (3GdJcGdjas; (3GdeMGSHIs; (3eMGSHI GdJcGdjas